Hukum Keluarga Islam Dalam Potret Interrelasi Sosial - J.M. Muslimin (AHKAM : Jurnal Ilmu Syariah, 2015)
Islamic Family Law has been studied for long time in many Faculties of Sharia. The need of establishing the Faculties itself was due to the existing social need: producing judges for Peradilan Agama (Islamic Court). It may be true, because of that reason the tendency of studying Islamic Family Law is almost going “no where”. The core of the study is running on the redundant condition. This writing tries to present an alternative sample to minimize redundancy. At the same time, the writing supports and strengthens the need for empirical legal research by using and correlating the law to social sciences. The substance of the writing describes the correlation between Islamic Family Law and some social factors in a comparative modelDOI: 10.15408/ajis.v15i1.2846